The tail that wagged the dog: What explains the persistent employment effect of the 10-day PPP funding delay? - Olga Gorbachev; Maria José Luengo-Prado; J. Christina Wang (Federal Reserve Bank of Boston, 2023)
This study explores the mechanisms explaining the large, persistent effect of the 10-day funding delay in the 2020 Paycheck Protection Program (PPP) on employment recovery during the COVID-19 pandemic, as estimated by Doniger and Kay (2021). We find that the top 1 percent of urban counties by population fully account for the significant effect of the delay on county-level employment. The strong correlation between worse loan delay and slower employment growth in these counties is due to a factor commonly omitted from analyses: The nature of business and the high rate of human interactions in major urban centers render these areas exceptionally and persistently vulnerable to infectious diseases. Moreover, we find that receiving more PPP funding and more transfers from other pandemic-related assistance programs contributed significantly more to local economic recovery compared with receiving PPP funds earlier.
Keywords: H81; G28; J21; E24; 330; COVID-19; Paycheck Protection Program; small business credit; remote work; employment